IDENTIFICATION OF MOLECULAR MARKER(S) FOR ROOT LENGTH IN RICE (ORYZA SATIVA L.) - REDDY, E. SIVA SANKAR; S. K. VERMA; S. M. XALXO; R. R. SAXENA; S. B. VERULKAR (The Bioscan, 2013)
An investigation was carried out to find the molecular markers associated with root length of rice using 271 Recombinant Inbred Lines (RILs) developed from Danteshwari X Dagad Deshi. Based on root pulling resistance and core sampling root scan data for root length, extreme DNA bulks of root length (11 lines in each bulk) were prepared. These bulks were subjected to Bulk segregant analysis with 186 SSR markers, followed by Co-segregation analysis with 14 SSR markers. From this analysis, it can be concluded that the markers HvSSR 01-80, HvSSR 0187, HvSSR 05-31, RM242, RM135, RM499, RM232, RM296 and RM26334 are associated with the trait. Among them RM242 located on chromosome 9 can be considered as good marker for root length in marker assisted selection.